Metered Dose Inhaler among Patients with Respiratory Disorders - Paudel Aryal, Kalpana; Rai, Nisha; Banstola, Ratna Shila (Journal of Nepal Health Research Council, 2025)
Background: Metered dose inhaler is the most recommended and efficient therapy for management of respiratory disorders but incorrect inhaler use has critical to get significant impact of medication. The study aimed to assess the knowledge and practice on Metered dose inhaler among patients with respiratory disorders. Methods: Cross-sectional study was conducted among 126 patients with respiratory conditions in 2021 in a teaching hospital. A structured questionnaire was used to assess knowledge on using Metered dose inhaler whereas checklist created by the WHO Guide to Good Prescribing was used to evaluate patient’s practice on inhalation technique. Results: The results showed that 74 (58.7%) of the patients were female and belonged to age group 66-80 years (mean/SD 63.35±11.803). Over half of the patients i.e., 66 (52%) had a satisfactory level of knowledge whereas, only 2 (1.6%) patients were aware on the waiting time between each puff of Metered dose inhaler. The results showed that only 3 (2.4%) patients had practiced correct technique on Metered dose inhaler. Conclusion: Though the higher proportion of the patients had satisfactory level of knowledge on Metered dose inhaler use but critical gap was seen in essential steps for using Metered dose inhaler. Healthcare providers should consider appropriate measure to increase the knowledge and correct use of Metered dose inhaler. That ultimately improves the quality of respiratory health of patients with respiratory disorders. Keywords: Knowledge; metered dose inhaler; patients; practice; respiratory disorders.